The frozen ground [videorecording (DVD)] - Walker, Scott, 1971-; Walker, Scott, 1971-; Cage, Nicolas, 1965-; Cusack, John, 1966-; Hudgens, Vanessa, 1988-; 50 Cent (Musician) (Lionsgate, 2013)
Inspired by the true story that follows Alaskan State Trooper Jack Halcombe, as he sets out to end the murderous rampage of Robert Hansen, a serial killer who has gone unnoticed for thirteen years. Risking his life, Halcombe goes on a personal manhunt to find the killer before the next body surfaces.